Nourishing law-students’ professionally-directed English-language communicative abilities including socio-perceptual skills - Emelianova, T.V. (Opción, 2019)
The goal of this paper is to determine key skills and abilities necessary for law-students to be effectively involved in professionally-directed English-language communication. The descriptive analysis was implemented to present key issues. This paper’s methodological bases are the conceptual provisions of researchers in linguistics, theory and methodology of teaching foreign languages, psycholinguistics, intercultural interaction, English for special purposes. In result, one of the indicators of the high level of law-students’ communicative competence development was their speech culture. In conclusion, law-students were shifted into the next gear by transforming into legitimate interlocutors with the only mission of getting their job done.